Yläkouluun siirtyneiden oppilaiden kalojen lajintuntemus - Puranen, Marko (2013)
Children are studying fishes in the 5th and 7th grades in Finland, so they get basic knowledge about fishes that live in Finland. In upper comprehensive school almost all pupils have tried fishing during their life. The aim of this study was to find out how well 7th grade students are able to identify fish species. In addition, I tried to identify factors that influence possible differences in these skills between the pupils. The material was collected from 12 upper comprehensive schools. The schools were located in three different regions. Each region had four schools, so that there were 2 urban and 2 countryside localities in each region. Altogether, 199 students participated in the survey. The survey included identification test of fish species and multiple choice questions. Pupils had to identify 8 different species that represented the most typical Finnish fish species. Results showed that the students identified on average half of the fish species. Pike and perch were the species that the students identified the best. Pike-perch and whitefish were the most difficult for the pupils. There were differences between sexes and living environments in the identification skills. Boys identified fish species better than girls. Students living in the countryside identified fish species better than students living in a detached house or an urban environment. Fishing as a hobby correlated the most with knowledge on fish species. Further, fishing was more common among boys. Even every fifth student had not studied fish species in primary school. Both youngsters from urban areas and countryside felt nature to be an important place. Students, who had fishing family members or friends, were more likely to fish by themselves. Therefore it is important that fishing is respected in the youngsters’ vicinity.